The Relationship Habits of Through Breakfast and Physical Activity with Abdominal Obesity in Nutrition Students - Wijayanti, Martha Ria; Adiningsih, Sri; Rachmah, Qonita (Universitas Airlangga, 2021)
Background : Abdominal obesity is obesity characterized by the accumulation of excess fat in the abdominal area. The risk of metabolic and cardiovascular disease may increase due to abdominal obesity. One of the factors associated with abdominal obesity is imbalance between energy intake and physical activity. Several studies have stated that skipping breakfast is associated with an increased risk of obesity with the tendency to consume high calorie foods to provide energy for activities.Objectives : The purpose of this study is to analyze the relationship between skipping breakfast, level of physical activity and obesity in nutrition students at Public Health Faculty, Airlangga University.Methods : This research is observational analytic with cross sectional design. The population in this study were nutrition students at Public Health Faculty, Airlangga University. The number of samples was 60 people which selected by proportional random sampling method. Data were collected include the measurements of waist circumference, interviews using respondent's identity questionnaire and physical activity recall 3 x 24 hours. Data were analyze with Spearman correlation test.Results : Based on the results, it was found that 33.3% of the respondents were obese. The results of statistical tests shows a negative correlation between skipping breakfast and abdominal obesity (p = 0.000). The results of this study also showed that there is no significant correlation between the level of physical activity and obesity (p = 0.618).Conclusions : Skipping breakfast was significantly associated with abdominal obesity in the young adult students group. Therefore, it is better if the habits of skipping breakfast can be replaced with breakfast habits to prevent abdominal obesity.